(The Economic and Social Impacts of begging in Egypt during the Period (2000 - 2016 - Hassan, Izzat Mallock Qenaoui (Journal of Economic, Administrative and Legal Sciences, 2017)
This research aims to analysis the begging phenomena in Egypt, types and motivations causing, next to recognize the economic and social effects resulting from it and to identify the most important obstacles that limit the fight against this phenomenon and propose appropriate solutions to reduce the aggravation in the future. The research supposed that there is a direct correlation between the poverty, inflation, unemployment and poor distribution of national income and the growing the phenomenon of begging in Egypt. The approach of descriptive analysis has been used to describe and analyze this phenomenon and the statement of reasons and motives, economic and social impacts, besides using social survey method through direct interview method with a random sample of beggars in the city of Cairo, and analysis of obtained data from the results of the research sample using a quantitative approach through statistical method. The results of research refer to that begging has negative effects on the national economy, related to the lack of contribution to the beggar in the GDP, it represents a burden on society and helps to increase crime rates and hamper the economic growth. The study suggested that support programs and policies to combat poverty as the main reason to beg through the empowerment of families from the socially and economically healthy sides to do their roles and ensure that their members to reduce the aggravation of this phenomenon in the future.